1800 Ga. Laws 157 - (:unkn) unknown (My University, 1770)
"WHEREAS it is necessary for the security and defence of this province from internal dangers and insurrections, that all persons resorting to places of public worship shall be obliged to carry fire arms
Keywords: REQUIRED POSSESSION